2019
DOI: 10.1021/acsami.9b14286
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polymer Microparticles with Tunable Shapes and Surface Textures for Enhancement of Dendritic Cell Maturation

Abstract: In this report, we present a facile approach to produce biodegradable polymeric microparticles with uniform sizes and controllable morphologies by blending hydrophobic poly­(d, l-lactic-co-glycolide) (PLGA) and amphiphilic poly­(d, l-lactic acid)-b-poly­(ethylene glycol) (PLA-b-PEG) in a microfluidic chip. Microparticles with tentacular, hollow hemispherical, and Janus structures were obtained after complete evaporation of the organic solvent by manipulating the interfacial behavior of emulsion droplets and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…In a separate work of Hussain and colleagues, the influence of surface textures and particle geometries on the immune effects of dendritic cell was investigated by culturing the cells with the presence of distinct kinds of anisotropic particles from microfluidics including smooth particles, tentacular particles with several tentacles, golf-like particles, bowl-like particles, particles with different roughness. 168 Results showed that particles in textured surfaces and non-spherical geometries had better amelioration on the activation of the dendritic cell because they could provide more contact points to dendritic cells.…”
Section: Cell Culturementioning
confidence: 97%
“…In a separate work of Hussain and colleagues, the influence of surface textures and particle geometries on the immune effects of dendritic cell was investigated by culturing the cells with the presence of distinct kinds of anisotropic particles from microfluidics including smooth particles, tentacular particles with several tentacles, golf-like particles, bowl-like particles, particles with different roughness. 168 Results showed that particles in textured surfaces and non-spherical geometries had better amelioration on the activation of the dendritic cell because they could provide more contact points to dendritic cells.…”
Section: Cell Culturementioning
confidence: 97%
“…A wide variety of post‐treatment techniques, including solvent‐absorbing/releasing, [ 109,110 ] general solvent evaporation, [ 111–121 ] microfluidic emulsification/emulsion–solvent evaporation, [ 122–128 ] electrospraying/solvent evaporation, [ 129–137 ] electrospinning/solvent evaporation, [ 138,139 ] templating method, [ 140–166 ] treatment on core–shell particles [ 167–173 ] and self‐assembly of polymer [ 174–176 ] have been developed for dimpled polymer particles syntheses.…”
Section: Dimpled Polymer Particlesmentioning
confidence: 99%
“…[105] Copyright 2017, American Chemical Society. microfluidic emulsification/emulsion-solvent evaporation, [122][123][124][125][126][127][128] electrospraying/solvent evaporation, [129][130][131][132][133][134][135][136][137] electrospinning/solvent evaporation, [138,139] templating method, treatment on core-shell particles [167][168][169][170][171][172][173] and self-assembly of polymer [174][175][176] have been developed for dimpled polymer particles syntheses.…”
Section: Post-treatment On Polymer Particlesmentioning
confidence: 99%
“…The pore size and diameters of particles were tuned by the polymer concentration and SDS concentration 25 . Recently, particles with tunable surface structures of biocompatible polymers were prepared by employing this method 12 . Hussain et al showed that poly(lactic‐ co ‐glycolic acid) (PLGA) particles with wrinkled and tentacle surfaces were prepared by adding PLGA‐ b ‐polyethylene glycol (PLGA‐ b ‐PEG).…”
Section: Droplet Microfluidic Assisted Preparation Of Monodispersed P...mentioning
confidence: 99%
“…Polymer particles with rough surfaces have great potential in surface‐sensitive biomedical applications, 9c,10 such as cell attachment, cell proliferation, biomolecular sensing, bioimaging, and biolabeling. In particular, some particles can serve as bionic microorganisms and pollen 11 and have been used as bionic pathogens and potential carriers of hapten for immunity 12 …”
Section: Introductionmentioning
confidence: 99%